Chapter La pianificazione integrale di Leonardo da Vinci. Implicazioni etiche, politiche e sociali - FALLANCA, Concetta (Territori, 2023)
Leonardo anticipates an integral, structuralist and ecological vision of the relationship between the territory and the city. The hydraulic and territorial systems he designs 'at the service' of cities and mobility show his unparalleled ability to 'govern' physiographic systems, combining climatic temperament with functional and hygienic reasons. The paper intends to observe and interpret the clues that confirm the original concreteness of its urban plans and projects aimed at giving precise answers to social needs, which are still incredibly topical today.